2022
DOI: 10.7861/clinmed.2020-1107
|View full text |Cite
|
Sign up to set email alerts
|

Utility of severity assessment tools in COVID-19 pneumonia: a multicentre observational study

Abstract: BackgroundSeverity scores in pneumonia and sepsis are being applied to SARS-CoV-2 infection. We aimed to assess whether these severity scores are accurate predictors of early adverse outcomes in COVID-19. MethodsWe conducted a multicentre observational study of hospitalised SARS-CoV-2 infection. We assessed risk scores (CURB65, qSOFA, Lac-CURB65, MuLBSTA and NEWS2) in relation to admission to intensive care or death within 7 days of admission, defined as early severe adverse events (ESAE). The 4C Mortality Sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Demir et al reported better performance in predicting COVID-19 mortality with 83.33% sensitivity, 90.43% specificity, and 0.942 AUC [ 16 ]. However, other authors have raised concerns about the reliance on the CURB-65 score to guide clinical decision-making in COVID-19 patient care, despite showing statistically significant differences in distinguishing between survivors and non-survivors, and there is an argument that the CURB-65 score is incapable of accurately estimating COVID-19-associated mortality due to the complexity and specific characteristics of COVID-19 disease and the presence of many risk factors [ 25 , 26 ]. Our study results indicates a good performance of the CURB-65 score as a prognostic tool, estimating patient mortality with a sensitivity of 75.00%, a specificity of 82.31%, YJI 0.57, AUC 0.834, and P < 0.0001, which supports its use for rapid triage of COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Demir et al reported better performance in predicting COVID-19 mortality with 83.33% sensitivity, 90.43% specificity, and 0.942 AUC [ 16 ]. However, other authors have raised concerns about the reliance on the CURB-65 score to guide clinical decision-making in COVID-19 patient care, despite showing statistically significant differences in distinguishing between survivors and non-survivors, and there is an argument that the CURB-65 score is incapable of accurately estimating COVID-19-associated mortality due to the complexity and specific characteristics of COVID-19 disease and the presence of many risk factors [ 25 , 26 ]. Our study results indicates a good performance of the CURB-65 score as a prognostic tool, estimating patient mortality with a sensitivity of 75.00%, a specificity of 82.31%, YJI 0.57, AUC 0.834, and P < 0.0001, which supports its use for rapid triage of COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Remdesivir, 33 dexamethasone 34 and other immunomodulatory drugs 35 like baricitinib continue to be used for those with severe disease, requiring oxygen to avoid progression to mechanical ventilation (where possible) and reduce the risk of dying. Management strategies are increasingly guided by the use of objective risk assessment measures of disease severity in both vaccinated and unvaccinated to prognosticate outcomes, e.g., the International Severe Acute Respiratory and Emerging Infections Consortium (ISARIC) score 36,37 …”
Section: Discussionmentioning
confidence: 99%
“…27,28 Vaccine-induced thrombotic thrombocytopenia (VITT), although predominant in recipients of adenovirus vector vaccines, 29 does not appear to recur with the second dose regardless of the type of vaccine and remains rarely, if at all, associated with mRNA vaccines. 30 Thirdly, diagnostic tests like antigen rapid tests (ART) 31 36,37 Pre-exposure prophylaxis using Tixagevimab and Cilgavimab (Evusheld) is now also available. 38…”
Section: Discussionmentioning
confidence: 99%